Hydrogen bonding effects on the (15)N and (1)H shielding tensors in nucleic acid base pairs - Czernek, J; Fiala, R; Sklenár, V (Journal of magnetic resonance (San Diego, Calif., 2000)
The results of systematic ab initio calculations of (15)N and (1)H chemical shielding tensors in the GC base pair as a function of hydrogen bond length are presented for the first time. The hydrogen bond length characterized by the distance r(N...N) between purine N1 and pyrimidine N3 was varied between 2.57 and 3.50 A and the chemical shift tensors were calculated by the sum-over-states density functional perturbation theory. It is shown that the hydrogen bond length has a strong effect on the chemical shielding tensor of both imino proton and nitrogen, on their orientation, and, as a consequence, on the relaxation properties of both nuclei. For a nitrogen nucleus not involved in hydrogen bonding, the shielding tensor is nearly axially symmetric and almost collinear with the bond vector. As the length of the hydrogen bond decreases, the least shielding component sigma(11) deflects from the N-H vector and the shielding tensor becomes increasingly asymmetric. The significance of the presented results for the analysis of relaxation data and the efficiency of TROSY effects together with a summary of the relevant shielding parameters are presented and discussed.
Keywords: izotopy dusíku; Cytosine; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Nitrogen Isotopes; párování bází; vodíková vazba; vodík; Guanine; guanin; cytosin; Base Pairing; Hydrogen; Hydrogen Bonding